P074 Significant efficacy and long term safety difference with taf-based str in naïve adults. (8th June 2017) - Arribas, Jose; Thompson, Melanie; Sax, Paul; DeJesus, Edwin; Clark, Amanda; Das, Moupali; McCallister, Scott
Abstract : Introduction: At Week(W) 48, elvitegravir/cobicistat/emtricitabine/tenofovir alafenamide (E/C/F/TAF) was statistically noninferior to E/C/F/tenofovir disoproxil fumarate(TDF) for the proportion of subjects with HIV-1 RNA <50 copies (c)/mL and had significant improvements in renal and bone safety endpoints. We report W144 data. Methods: ARV-naïve participants randomised 1:1 to receive E/C/F/TAF or E/C/F/TDF. W144 viral suppression (HIV-1-RNA <50 and <20 c/mL) by FDA snapshot analysis, pre-defined bone and renal safety, and tolerability endpoints are reported. Results: 1, 733 HIV-infected adults were randomised and treated: 15% women, 43% non-white, 23% viral load (VL) >100, 000 c/mL. Median baseline characteristics: age 34 years, CD4 count 405 cells/µL, and VL 4.58 log10 c/mL. At W144, E/C/F/TAF met pre-specified criteria for both non-inferiority and superiority to E/C/F/TDF by FDA snapshot algorithm (HIV-1-RNA <50 and <20 c/mL) (Table 1). Mean decrease in BMD was significantly less in the E/C/F/group for lumbar spine and hip (Table1). Multiple measures of renal safety were significantly better for participants on E/C/F/TAF (Table). No cases of renal tubulopathy in the E/C/F/TAF group vs 2 on E/C/F/TDF. No participants on E/C/F/TAF had renal-related discontinuations vs 12 on E/C/F/TDF (p<0.001). Participants on E/C/F/TAF had greater increases in lipids. Discussion: E/C/F/TAF was significantly superior than E/C/F/TDF, driven by fewer participants on E/C/F/TAF with no W144 data. E/C/F/TAF continued to have a statistically superior bone and renal safety profile compared with E/C/F/TDF, demonstrating significant safety advantages over E/C/F/TDF through 3 years of treatment. Individuals on E/C/F/TAF had greater plasma lipid changes, but proportions starting lipid-lowering therapy were comparable.